Empowering vocational teachers through digital innovation: Enhancing QR code-based learning media - Hidayat, Nuzul; Sardi, Juli; Putra, Rido; Ranuharja, Fadhli; Ismi, Riwayatul; Jamhur, Annisak Izzaty (Universitas Muhammadiyah Magelang, 2025)
The development of digital technology requires vocational education (SMK) teachers to be able to develop innovative learning media, such as QR codes, to support 21st-century learning. This community service activity aimed to improve the skills of teachers at SMKN 1 Padang Panjang in designing and implementing QR code-based digital learning media integrated with the Activities Digital Learning (ADL) concept. This activity involved 20 teachers through stages of socialization, training, workshops, hands-on practice, and mentoring. The materials covered AI-assisted digital module creation, media design (Canva), video production (CapCut), and QR Code integration into ADL. The results of the pre-test and post-test evaluation showed an average increase of 35% in teachers’ digital skills. Furthermore, each teacher successfully created at least one ready-to-use QR code-based learning media product. This program also successfully established a collaborative network among teachers to support the sustainability of digital innovation at the school.